Examen Especial a las Cuentas Maquinarias y Equipos y Vehículos del Gobierno Autónomo Descentralizado del Cantón Gonzanamá, Periodo 1 de enero al 31 de diciembre del 2015 - SOTO LUDEÑA, HUGO FERNANDO (2018)
The thesis work called Special Examination of Machinery Accounts and Equipment and Vehicles of the Decentralized Autonomous Government of Canton Gonzanama, focused on the evaluation of the internal control system implemented by the entity, determine the reasonableness of the balances presented in the financial statements and In the same way verify the degree of compliance with the legal provisions. For the first development, a previous visit to the Entity's facilities was made as often as necessary to obtain sufficient and competent information that would lead to the development and fulfillment of the three phases of the special examination; Began with the PLANNING, the preliminary planning where the recognition of the entity was realized; We continued with the specific planning where the internal control system was evaluated using the questionnaire method, in order to examine the risk and based on it select the special examination tests to be applied, therefore adopt the most appropriate techniques that allow To qualify the reasonableness of the balances presented by the Financial Statements, in the second phase of the EXECUTION, we applied the techniques and compliance tests, analytical and substantive, then to culminate we have the phase of COMMUNICATION OF RESULTS, the results obtained were elaborated The special review report containing the conclusions and recommendations aimed at strengthening the control and use of the entity's long-lived assets subject to the review.